Determination of ibuprofen enantiomers in human plasma by HPLC–MS/MS: validation and application in neonates. (June 2016) - Chen, Tingting; Li, Qin; Lu, Jinmiao; Yu, Chen; Chen, Chao; Li, Zhiping
Aim: An adaptive method to determine ibuprofen enantiomers with limited volume of plasma required is necessary for investigating PK of ibuprofen in neonates.Results: Enantiomer separation was achieved on a Lux cellulose 3 column with mobile phase consisting of methanol water (85:15, v/v) and formic acid (0.0075%) at isocratic rate of 0.2 ml/min. Calibration curve is linear for each enantiomer at the range of 0.1–60 μg/ml. Validation was conducted and results met requirements regarding to intra- and inter-run precision, accuracy and recovery. No matrix effect or interference was observed from neonatal plasma or comedications. Only 20 μl of plasma was requested in this study.Conclusion: This assay was specific and reliable to quantify ibuprofen enantiomers in neonate plasma.